Identification of multi-input multi-output systems using combined direct and indirect methods - Faisal, A. (Trans Tech Publications Ltd, 2014)
Successful deployment of cooperative decentralized model predicative control needs reasonably accurate subsystem interactions models. Processes in which open-loop tests are not permitted, closed-loop identification of subsystems interactions is crucial. An approach that combines the direct and indirect methods of closed-loop identification is proposed in this paper. It is shown that full dynamics of MIMO systems can be determined following a two-steps identification procedure. A representative case study is used to demonstrate the efficacy of the proposed approach. Â© 2014 Trans Tech Publications, Switzerland.